2001
DOI: 10.1016/s0960-9822(01)00329-3
|View full text |Cite
|
Sign up to set email alerts
|

Histone variant H2A.Z is required for early mammalian development

Abstract: Fundamental to the process of mammalian development is the timed and coordinated regulation of gene expression. This requires transcription of a precise subset of the total complement of genes. It is clear that chromatin architecture plays a fundamental role in this process by either facilitating or restricting transcription factor binding [1]. How such specialized chromatin structures are established to regulate gene expression is poorly understood. All eukaryotic organisms contain specialized histone variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
257
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(266 citation statements)
references
References 15 publications
6
257
0
3
Order By: Relevance
“…46 Moreover in yeast, the deletion of either the Gal4 or Pho4 activators did not influence the ability of H2A.Z to be enriched at model target genes of these respective activators (Lemieux K and Gaudreau L, unpublished data). 47 Conversely, in human cells, results obtained by our and other laboratories suggest that targeting of H2A.Z, by virtue of the p400 or SRCAP such as Tetrahymena thermophila, 15 Xenopus laevis, 16,17 Drosophila melanogaster 18,19 and mice, 20 suggesting that it may provide distinct functions among different organisms. In budding yeast, loss of H2A.Z leads to defects in transcriptional activation, alterations in transcriptional silencing, and increased chromosome loss.…”
Section: H2az and Dna Methylationmentioning
confidence: 70%
“…46 Moreover in yeast, the deletion of either the Gal4 or Pho4 activators did not influence the ability of H2A.Z to be enriched at model target genes of these respective activators (Lemieux K and Gaudreau L, unpublished data). 47 Conversely, in human cells, results obtained by our and other laboratories suggest that targeting of H2A.Z, by virtue of the p400 or SRCAP such as Tetrahymena thermophila, 15 Xenopus laevis, 16,17 Drosophila melanogaster 18,19 and mice, 20 suggesting that it may provide distinct functions among different organisms. In budding yeast, loss of H2A.Z leads to defects in transcriptional activation, alterations in transcriptional silencing, and increased chromosome loss.…”
Section: H2az and Dna Methylationmentioning
confidence: 70%
“…However, the molecular and developmental mechanisms controlling pluripotency and differentiation of ES cells are largely unknown, and only a very limited number of genes has so far been shown to affect the fate decisions of inner cell mass (ICM) or ES cells. These genes include Oct4, Fgf4, H2az, Foxd3, Nanog, and Sox2 (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: E Mbryonic Stem Cells (Es Cells) Are Able To Form All Cell Tmentioning
confidence: 99%
“…Our present study showed that there were some differences in NBA, but not in the TNB among genotypes, suggesting that pH2AFZ gene is related to fetal survival but not ovulation rate. Faast et al (2001) observed that heterozygous H2A.Z 1/2 mice appeared normal and were fertile, but none were homozygous for the H2A.Z mutation. This indicated that a lack of functional H2AFZ led to embryonic lethality.…”
Section: Resultsmentioning
confidence: 97%
“…H2AFZ gene has been characterized in the human (Hatch and Bonner, 1988, 1990and 1995, mouse (Faast et al, 2001), cow (Ball et al, 1983), rat (NM_022674) and other species. Mice deficient in H2AFZ died early in development, i.e., around the time of implantation (Faast et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation